Understanding older adults’ smartphone addiction in the digital age: empirical evidence from China - Xu, Yujing; Zeng, Kai; Dong, Lucong; Zheng, Xiaofen; Si, Yuxiu (Frontiers in Public Health, 2023)
Despite an increasing number of elderly individuals addicted to smartphones, this fact has gone somewhat unnoticed by researchers. Smartphone addiction among adolescents has been well documented, but smartphone addiction among older people in the digital era deserves more attention. Based on the unique characteristics of elderly individuals, this study investigates smartphone addiction in middle-aged and older adults from two perspectives: subjective cognitive decline and family relationship conflict. Through a survey of 371 elderly individuals in China, this study shows that subjective cognitive decline and family relationship conflict in elderly individuals affect their smartphone addiction through a sense of alienation. In addition, their perceived power moderates the relationship between alienation and smartphone addiction. This study offers fresh perspectives on how to explore smartphone addiction in elderly individuals and sheds light on how to enhance their quality of life in their later years.